Honoring Children’s Ways of Knowing: A Story of Trust and Transformation in a Kindergarten Classroom (LEARNing Landscapes, 2019)
This article spotlights the transformation of a kindergarten classroom culture as told through the story of selecting and naming a class pet, emphasizing the teacher’s understanding of children’s ways of knowing and the role of trust in building an inclusive and equitable classroom environment. Bronfenbrenner’s bioecological systems theory serves as a lens in understanding the teacher’s efforts to build a culture respectful of each individual child, the group as it formed, and class’s identity in the broader learning community. The seemingly simple story is considered through the concept of rich normality, which recognizes the potential of everyday moments and experiences.
Keywords: trust; transformation; ways of knowing; inclusive/equitable classrooms; rich normality